Task‐dependent function of striatal cholinergic interneurons in behavioural flexibility. (2nd December 2017) - Okada, Kana; Nishizawa, Kayo; Setogawa, Susumu; Hashimoto, Kouichi; Kobayashi, Kazuto
Abstract: Flexible switching of behaviours depends on integrative functioning through the neural circuit connecting the prefrontal cortex and the dorsomedial striatum (DMS). Although cholinergic interneurons modulate striatal outputs by diverse synaptic mechanisms, the roles of cholinergic interneurons in the DMS appear to vary among different models used to validate behavioural flexibility. Here, we conducted immunotoxin‐mediated cell targeting of DMS cholinergic interneurons and examined the functions of these interneurons in behavioural flexibility, with the learning conditions differing in trial spacing and discrimination type in a modified T‐maze. Elimination of the DMS cholinergic cell group normally spared reversal learning in place discrimination with an intertrial interval (ITI) of 15 s, but it impaired the reversal performance in response discrimination with the same ITI. In contrast, DMS cholinergic elimination resulted in enhanced reversal performance in both place and response discrimination tasks with a 10‐min ITI and accelerated the reversal of response discrimination with a 20‐min ITI. Our previous study also showed an enhanced influence of cholinergic targeting on place reversal learning with a 20‐min ITI, and the present results demonstrate that DMS cholinergic interneurons act to inhibit both place and response reversal performance with a relatively longer ITI, whereas their functions differ between types of reversal performance in the tasks with a shorter ITI. These findings suggest distinct roles of the DMS cholinergic cell group in behavioural flexibility dependent on the trial spacing and discrimination type constituting the learning tasks. Abstract : Cell targeting of striatal cholinergic interneurons highlights that these neurons act to suppress both place and response reversal tasks with a relatively longer intertrial interval (ITI), whereas their functions facilitate the response reversal, not influencing the place reversal in the tasks with shorter ITI. Our results suggest distinct roles of cholinergic interneurons in flexible switching of behaviours dependent on the trial spacing and discrimination type constituting the learning tasks.